2013
DOI: 10.1371/journal.pone.0056964
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Mucosa-Associated E. coli Producing Cyclomodulin and Genotoxin in Colon Cancer

Abstract: Some Escherichia coli strains produce toxins designated cyclomodulins (CMs) which interfere with the eukaryotic cell cycle of host cells, suggesting a possible link between these bacteria and cancers. There are relatively few data available concerning the colonization of colon tumors by cyclomodulin- and genotoxic-producing E. coli. We did a qualitative and phylogenetic analysis of mucosa-associated E. coli harboring cyclomodulin-encoding genes from 38 patients with colorectal cancer (CRC) and 31 with divertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
429
7
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 439 publications
(487 citation statements)
references
References 70 publications
(83 reference statements)
15
429
7
4
Order By: Relevance
“…Acquisition of protumoral function by macrophages is directly influenced by tumor microenvironment. As several independent studies have reported high colonization by E. coli of adenomas and carcinomas in colon cancer patients, [15][16][17][18][19] we have analyzed the effect of such a microbial environmental factor on COX-2 expression in human macrophages. Phagocytic uptake of pathogens by macrophages results in the formation of vacuoles that rapidly evolve into bactericidal Figure 3 Intramacrophagic persistence of E. coli strains isolated from colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquisition of protumoral function by macrophages is directly influenced by tumor microenvironment. As several independent studies have reported high colonization by E. coli of adenomas and carcinomas in colon cancer patients, [15][16][17][18][19] we have analyzed the effect of such a microbial environmental factor on COX-2 expression in human macrophages. Phagocytic uptake of pathogens by macrophages results in the formation of vacuoles that rapidly evolve into bactericidal Figure 3 Intramacrophagic persistence of E. coli strains isolated from colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,33 Bacteria were grown routinely in Luria Bertani (LB) broth or on LB agar plates overnight at 37 1C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Interestingly, molecular analyses of these strains have revealed that they frequently harbor in their genome one or several pathogenic islands responsible for the production of toxins. 21,22 These toxins can induce DNA damage and/or affect the cellular cycle. E. coli harboring cytotoxic necrotizing factor (Cnf) and cytolethal distending toxin (Cdt) are significantly associated with CRC biopsies.…”
mentioning
confidence: 99%
“…E. coli harboring cytotoxic necrotizing factor (Cnf) and cytolethal distending toxin (Cdt) are significantly associated with CRC biopsies. 21 However, the toxin most frequently associated with E. coli colonizing CRC is colibactin. 21,22 Colibactin is a genotoxic polyketide non-ribosomal peptide (PK-NRP) not yet purified and synthetized by the pks genomic island.…”
mentioning
confidence: 99%